FREE NUTRITIOUS MEAL POLICY FROM THE PERSPECTIVE OF FOOD SECURITY, EDUCATION, AND SOCIAL JUSTICE - Rasyid, Hilman; Ginanjar Masruri; Heru Nugraha; Ara Hidayat (STAI Ma'had Aly Al-Hikam Malang, 2025)
Abstract This study examines the implementation of the Free Nutritious Meal (MBG) policy in schools as a strategy to strengthen food security, improve education, and realize social justice. The study is motivated by high levels of nutritional vulnerability among school-age children, which affect learning concentration, attendance, and academic achievement. This research employs a library research and qualitative-critical analysis approach, reviewing relevant scientific journals from the last five years on MBG, food policy, education, and social development. Results indicate that MBG significantly enhances children’s access to nutritious food, promotes educational participation, and reduces social inequality through equitable and inclusive benefit distribution. Additionally, MBG supports local economic empowerment by involving local food producers and contributes to sustainable development by integrating social, economic, and environmental aspects. In conclusion, MBG is a multidimensional public policy effectively addressing nutritional, educational, and social inequality issues while supporting sustainable national development goals. Keywords: Free Nutritious Meal, Food Security, Education, Social Justice, Sustainable Development Abstrak Penelitian ini membahas implementasi kebijakan Makan Bergizi Gratis (MBG) di sekolah sebagai strategi untuk memperkuat ketahanan pangan, meningkatkan pendidikan, dan mewujudkan keadilan sosial. Latar belakang penelitian ini adalah tingginya angka kerawanan gizi pada anak usia sekolah yang berdampak pada konsentrasi belajar, kehadiran, dan prestasi akademik. Penelitian menggunakan pendekatan studi pustaka dan analisis kualitatif-kritis, dengan telaah literatur jurnal ilmiah lima tahun terakhir yang relevan mengenai MBG, kebijakan pangan, pendidikan, dan pembangunan sosial. Hasil penelitian menunjukkan bahwa MBG secara signifikan meningkatkan akses anak-anak terhadap makanan bergizi, mendorong partisipasi pendidikan, serta mengurangi ketimpangan sosial melalui distribusi manfaat yang merata dan inklusif. Selain itu, MBG mendukung pemberdayaan ekonomi lokal melalui keterlibatan produsen pangan setempat dan berkontribusi terhadap pembangunan berkelanjutan melalui integrasi aspek sosial, ekonomi, dan lingkungan. Kesimpulannya, MBG merupakan kebijakan publik multidimensi yang efektif mengatasi isu gizi, pendidikan, dan ketimpangan sosial sekaligus mendukung tujuan pembangunan nasional yang berkelanjutan. Kata kunci: Makanan Bergizi Gratis, Ketahanan Pangan, Pendidikan, Keadilan Sosial, Pembangunan Berkelanjutan